Perturb and Observe Maximum Power Point Tracking Technique with PID Controller for a Wind Power System - K. Keerthi Sri; K. Rama Sudha (International Journal of Advanced Control and System Engineering, 2023)
The wind power generation system has a significant growth worldwide over the past four decades. The wind power generation system has strong coupling and linear characteristics which makes it a complicated electromechanical system. The power control strategy has a higher impact on the overall performance as the wind power generation is operated at variable and random wind speed conditions. PID control is the most used control algorithm in industrial applications. PID controllers are known for their robust performance in a wide range of operating conditions and their functional simplicity which allows engineers to work in a simple manner. The efficiency of the wind power generation is improved by proposing a PID (Proportional Integral Derivative) controller based MPPT (Maximum Power Point Tracking) scheme in the LabVIEW platform. The wind turbine is modelled in accordance with the mathematical equations in LabVIEW platform. The permanent magnet synchronous generator (PMSG) and rectifier-converter system is modelled in the LabVIEW Multisim platform. The Perturb and Observe MPPT control strategy with a PID controller is introduced to the system to obtain maximum power. The simulation tests are performed under various wind speeds. The results obtained demonstrate that PID based MPPT technique is efficient to improve wind power generation.
Keywords: LabVIEW; MPPT (maximum power point tracking); Multisim; PID-controller; Wind power generation